2018
DOI: 10.1007/s40617-018-00283-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Treatment of Pica on a Preschool Playground

Abstract: Appropriate use of function-based assessments and interventions is crucial for improving educational outcomes and ensuring the well-being of children who engage in dangerous problem behaviors such as pica. A function-based assessment was conducted for a child engaging in pica in an inclusive childcare setting. Results suggest pica was maintained by access to adult attention. Function-based interventions were developed, assessed, and shared with the child's teaching team. Follow-up data suggest that his teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In addition to the study being conducted in an efficient format, the methodology described in Study 2 of this paper described a process for safely conducting FAs of pica in a home. This aspect of the study replicated previous studies focused on assessing pica in naturalistic settings (i.e., Ledford et al, 2019;Taylor, 2020). While pica can be dangerous and require safety precautions, hospital or clinical settings may not be available to all practitioners attempting to assess the behavior.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to the study being conducted in an efficient format, the methodology described in Study 2 of this paper described a process for safely conducting FAs of pica in a home. This aspect of the study replicated previous studies focused on assessing pica in naturalistic settings (i.e., Ledford et al, 2019;Taylor, 2020). While pica can be dangerous and require safety precautions, hospital or clinical settings may not be available to all practitioners attempting to assess the behavior.…”
Section: Discussionsupporting
confidence: 78%
“…One reason is that there are few published assessments of pica that describe FA methodology used in settings other than hospitals or other contrived clinical settings. Two studies that do describe FAs of pica in applied settings are Ledford et al (2019) and Taylor (2020). Ledford et al, described procedures for conducting a FA of pica on a preschool playground, and Taylor described procedures for conducting a FA on pica within a home setting.…”
Section: A Brief Assessment Of Picamentioning
confidence: 99%
“…A child with pica condition in an inclusive childcare setting, a functionbased evaluation was performed. Results indicate that pica was preserved by access to adult attention [8].…”
Section: Introductionmentioning
confidence: 86%
“…Results of a functional behavior assessment conducted 1 month prior to study onset indicated that SIB was maintained by access to tangible items, access to attention, and escape from activities and transitions. The functional behavior assessment included both direct (trial-based functional analyses, direct observation) and indirect (teacher interviews) assessments, which were used to develop his BIP under the supervision of two doctoral-level certified behavior analysts (Ledford et al, 2018). Elliot’s classroom team implemented the BIP inconsistently prior to study onset, which had decreased the frequency and intensity of Elliot’s SIB.…”
Section: Methodsmentioning
confidence: 99%